Riau University Students' Perceptions of the Role of the Pekanbaru City Election Smart House (RPP) - Apriyanti, Riva; Erlinda, Sri; Primahardani, Indra (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research was based by the phenomenon of low curiosity among Riau University students regarding election smart homes (RPP), this is in line with the results of interviews with 10 Riau University students, of whom 6 students did not know what an election smart home was or the role of an election smart home. This shows how low the curiosity of Riau University students is, so that an attitude of indifference or not caring about the existence of this election smart house (RPP) appears. The formulation of the problem in this research is what is the perception of Riau University students regarding the role of the Pekanbaru City Election Smart House (RPP). The population in this study was Riau University students, totaling 35,395 people. (PDDikti 2022) and the sample taken in this research was 100 respondents taken from each faculty, 10 people using the Kouta Sampling Technique. The data collection methods used in this research are interviews, questionnaires and documentation. Based on the results of research and information data, the role of the smart home election (RPP) is shown by the percentage of respondents who answered Very Playful, amounting to 23.8%, plus the results of the percentage of respondents who answered Playing a Role, which was 60.3%, namely the sum of 84.1% which is located in the range 75.01%-100%. Thus, it can be concluded that the Perception of Riau University Students towards the Role of the Pekanbaru City Election Smart House (RPP) is in the Very Important category.